Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
Three elderly women sit by the roadside.
Colour; Black and white; Style: Landscape: Other: Bordered, Undivided
Keywords: Postcards; Trinidad and Tobago; Elderly women; Elderly poor